SEGREGASI GENDER DALAM MANAJEMEN PESERTA DIDIK DI LEMBAGA PENDIDIKAN ISLAM - Thoriquttyas, Titis (Martabat: Jurnal Perempuan dan Anak, 2018)
ABSTRACT Tracing back through the historical line of Indonesian Islamic Schooling, the management model of gender segregation can be analyzed explicitly. This research will trace the model of gender’s segregation which concerned on the management of learner and it involving the indicators of gender analysis, namely the access and the participation as well as the Gender Analysis Pathway (GAP). This research conducted in MA Sunan Pandanaran Yogyakarta due to the some scientific reasons. From the brief explanation above, the research will be concerned on: First, the management of learner and its relevance on the model of gender’s segregation. Second, Its analytical relationship based on the indicators of GAP and the indicator of access as well as participation of learners. To sum up, Islamic school had the unique model of relationship between gender and the management model in the learning process; it is classified into the biased-gender and the neutral-gender Keywords: Gender Segregation; Islamic School; The Management of Learners   ABSTRAK Menelusuri kembali melalui kajian kesejarahan dari perkembangan lembaga pendidikan islam di Indonesia, model manajemen dengan mengedepankan segregasi gender dapat ditemui secara eksplisit. Penelitian ini akan mengkajinya model segregasi gender yang berfokus pada tata kelola peserta didik dan itu melibatkan analisis indikator gender yang meliputi indikator Akses dan Partisipasi serta analisis melalui GAP. Penelitian ini dilakukan pada MA Sunan Pandanaran Yogyakarta dilatarbelakangi oleh beberapa pertimbangan akademik. Dari penjelasan singkat diatas, penelitian ini akan berfokus pada: 1). Tata kelola peserta didik dan kaitannya dalam model segregrasi gender. 2). Analisis keterkaitannya didasarkan pada indikator GAP dan indikator akses serta partisipasi dari peserta didik. Kesimpulannya, Lembaga pendidikan Islam mempunyai model relasi yang unik antara konsep gender dan model tata kelola peserta didiknya dalam proses pembelajarannya, hal itu diklasifikasikan dalam dua model, model bias gender dan model netral gender. Kata Kunci: Segregasi Gender; Lembaga Pendidikan Islam; Tata Kelola Peserta didik.